2017
DOI: 10.1007/s00134-016-4669-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a condolence letter on grief symptoms among relatives of patients who died in the ICU: a randomized clinical trial

Abstract: In relatives of patients who died in the ICU, a condolence letter failed to alleviate grief symptoms and may have worsened depression and PTSD-related symptoms. Trial registration Clinicaltrials.gov Identifier: NCT02325297.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
137
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(148 citation statements)
references
References 39 publications
2
137
2
7
Order By: Relevance
“…6 Some well-designed palliative care interventions have not resulted in significant improvements in patient or family outcomes and, in some cases, have been associated with worsened outcomes. [7][8][9] Given the increasing interest in developing interventions, payment plans, and policies that enhance palliative care, it is important to document that such interventions, plans, and policies improve quality of care without unintended consequences. 10 There is also increasing interest in ensuring highquality, population-based care for seriously ill patients and their families across settings, including hospital, clinical, longterm care facility, and home, and using quality measurement to ensure accountability for this care.…”
mentioning
confidence: 99%
“…6 Some well-designed palliative care interventions have not resulted in significant improvements in patient or family outcomes and, in some cases, have been associated with worsened outcomes. [7][8][9] Given the increasing interest in developing interventions, payment plans, and policies that enhance palliative care, it is important to document that such interventions, plans, and policies improve quality of care without unintended consequences. 10 There is also increasing interest in ensuring highquality, population-based care for seriously ill patients and their families across settings, including hospital, clinical, longterm care facility, and home, and using quality measurement to ensure accountability for this care.…”
mentioning
confidence: 99%
“…A randomized trial of condolence letters from ICU physicians and nurses to family members 15 days after a death in the ICU had a surprising result, showing the letter was associated with increased symptoms of depression and post-traumatic stress disorder (PTSD) at 6 months [3]. This study suggests that routine condolence letters are not helpful-at least at 6 months-and highlights the importance of evaluating interventions we think will improve patient-and family-centered outcomes.…”
mentioning
confidence: 91%
“…Hospital length of stay was shorter with the intervention and, among patients who died in the ICU, ICU length of stay was shorter, yet ICU and hospital mortality were similar. This study presents an important model for integrating palliative care into the ICU.A randomized trial of condolence letters from ICU physicians and nurses to family members 15 days after a death in the ICU had a surprising result, showing the letter was associated with increased symptoms of depression and post-traumatic stress disorder (PTSD) at 6 months [3]. This study suggests that routine condolence letters are not helpful-at least at 6 months-and highlights the importance of evaluating interventions we think will improve patient-and family-centered outcomes.…”
mentioning
confidence: 99%
“…Among the many potential contributors to these adverse bereavement outcomes are the circumstances surrounding and processes of limiting life support. This hypothesis is supported by evidence that ICU deaths are commonly preceded by decisions to withdraw life support [3], and evidence that both ICU processes of care [4,5] and behaviors of ICU clinicians [1,6] near the end of life can influence family members' post-ICU psychological outcomes. Thus, uncertainty regarding which approaches to withdrawing mechanical ventilation are least distressing for patients and families [7,8] represents an important area for rigorous investigation.…”
mentioning
confidence: 94%
“…Although several measures have been found to be reliable and valid, responsiveness to ICUbased interventions has been a much more elusive goal. Few studies have found changes in the Impact of Events Scale (IES) [4,5] among family members of critically ill patients, and even fewer have shown responsiveness of the Inventory of Complicated Grief (ICG).…”
mentioning
confidence: 99%